A study on correlation between brand identity integrity and innovation capabilities - KAÇAR, DUYGU (My University, 2016)
Al design manufacturers (ODM) before starting their own brand manufacture (OBM).Therefore, those companies started production basically by producing for other companies, while they started product design activities by designing for other brands. Design fixation is defined as the tendency to be fixated to design solutions that are previously seen before starting a design process (Jansson & Smith, 1991). It may be hypothesized that, it will take longer to develop a brand identity in an upcoming product concept for those companies that have an OEM and ODM background along with an incremental innovation capability. In their studies, Dell’Era and Verganti (2007) also found that companies that have a radical innovator character seem to have a more integrated brand identity when compared to incremental innovators. It is also hinted in literature that companies which have OEM and ODM background have difficulties about transitioning to build more radical innovations (Hobday, 1998). In this study, brand identity integrity of companies that have an OEM and ODM background are evaluated along with others that have more radical innovation capabilities. This evaluation of brand identity integration is conducted through DFA. The DFA method is originally used for analyzing the brand identity characteristics of a company; however, in this study it is used in a more critical way to observe how scattered the product portfolios are for companies with OEM and ODM backgrounds. As the result of the study, it may be claimed that companies that could become affected by design fixation, may have less integrated brand identities.
Keywords: Mühendislik ve Teknoloji; Endüstri Ürünleri Tasarımı; Engineering and Technology; Industrial Design; Mühendislik, Bilişim ve Teknoloji (ENG); Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; MİMARİ; Engineering, Computing & Technology (ENG); Arts & Humanities (AHCI); ARTS & HUMANITIES; ARCHITECTURE; Mimari; Fizik Bilimleri; Architecture; Physical Sciences